2020
DOI: 10.1016/j.heliyon.2020.e04539
|View full text |Cite
|
Sign up to set email alerts
|

REAC neurobiological treatments in acute post-traumatic knee medial collateral ligament lesion

Abstract: Objective Physical traumas can lead to unconscious neuropsychical alterations, which can compromise rehabilitation result and functional recovery. Aim of this interventional study is to verify if neurobiological Radio Electric Asymmetric Conveyer (REAC) treatments Neuro Postural Optimization (NPO) and Tissue Optimization (TO) are able respectively to improve neuro psychomotor strategies and facilitate recovery process in medial collateral ligaments (MCL) lesions of the knee. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The REAC peculiar mechanism of action does not consist in the administration of an exogenous current, but it determines the progressive restoration of the asymmetries of electrical charges in tissues [ 11 - 13 ]. This phenomenon allows the recovery of ionic flows and therefore of the cellular EBA, which is essential to activate the fine reparative processes of the tissues [ 11 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The REAC peculiar mechanism of action does not consist in the administration of an exogenous current, but it determines the progressive restoration of the asymmetries of electrical charges in tissues [ 11 - 13 ]. This phenomenon allows the recovery of ionic flows and therefore of the cellular EBA, which is essential to activate the fine reparative processes of the tissues [ 11 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The REAC functional recovery of the correct EBA is able to promote reparative [ 11 , 14 , 15 ] and regenerative processes [ 16 - 18 ], up to determining phenomena of direct cellular reprogramming [ 12 , 13 , 19 , 20 ]. The possibility of obtaining refined reparative processes in a short time is particularly useful when it is desirable to achieve results that are also aesthetically pleasing, such as in the cases reported in this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…Barcessat et al demonstrated that REAC technology appears to be effective in reducing anxiety and stress. Thus, if we consider anxiety and stress as factors involved in atypical swallowing, we can assume that the bioelectrical modulation provided by REAC may favor the correction of the swallowing mechanism in patients with atypical swallowing (5).…”
Section: Lorenzini Et Al 2016mentioning
confidence: 99%
“…The radio electric asymmetric conveyer (REAC) technology aims to elicit cellular reprogramming activity and modulate adaptive responses in the body by restoring the balance of cellular endogenous bioelectric fields (1). It has been the target of studies in diverse areas of health sciences such as neurology (2,3), orthopedics (4,5), gerontology (6), cardiology (7), rheumatology (8) and histopathology (9)(10)(11). The basis for achieving the desired effects of REAC technology is the endogenous bioelectricity which affects neural and cellular processing mechanisms and, under pathological conditions, would be unbalanced (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation